Studies on Antibacterial Activity, Phytochemical Analysis of Stevia rebaudiana (Bert.) - An Important Calorie Free Biosweetner - and C.V.Naidu3*, D. Preethi1, T.M.Sridhar2, P.Josthna2 (Journal of Ecobiotechnology, 2011)
Stevia rebaudiana is an outstanding herb bearing leaves of very refreshing sweet taste and remarkable health promoting activities.Ã‚Â The herb is nutrient rich, containing substantial amounts of protein, calcium, phosphorous, sodium, magnesium, zinc, rutin, vitamin A, vitamin C and other nutrients, yet has no caloric value.Ã‚Â Six solvent extracts from leaf, three solvent extracts from flower of stevia were assayed for in vitro antibacterial activity against pathogenic bacteria such as Bacillus subtilis, Klebsiella pneumonia, Proteus vulgaris, Streptococcus pneumoniae, Staphylococcus aureus and Pseudomonas fluorescence, the zone of inhibition were compared with different standard antibiotics.Ã‚Â Phytochemical screening of the crude extracts revealed the presence of secondary compounds such as alkaloids, flavonids, steroids, tannins and phenols. The organic solvent extracts of flowers are very active against the tested bacterial stains when compared with leaf extracts.Ã‚Â Among the entire extracts petroleum ether flower extract showed high activity (11-13 mm zone of inhibition) on all the tested organisms.Ã‚Â Petroleum ether leaf and flower extracts gave very low MIC values. Petroleum ether flower extract gave lowest MIC values (0.390 to 1.562 Ã‚Âµg/ml) against all the bacterial isolates tested.